Edukasi Kompleksitas dan Permasalahan Perasuransian di Propinsi Nusa Tenggara Timur - Jefirstson Richset Riwukore (Gapenas Publisher, 2022)
The purpose of implementing community service activities (PkM) is to educate on the complexity of insurance, then evaluate and analyze insurance problems. This PkM implementation method uses lecture and discussion techniques, which are generally known as the focus group discussion (FGD) method. Activity partners are determined by purposive sampling technique (deliberately) based on the organizational structure consisting of the insurance assignment area. Based on this, the participants are determined by quota sampling technique, namely, the PkM activity participants are the direct leaders of the organization with the highest rank/position/class, ± 7 Heads or Organizational Directors. In addition, this FGD involved customers from each insurance industry with a quota of ± 1 person. Thus the participants who took part in this PkM activity were ± 21 people. The urgency of implementing this PkM is to educate participants regarding the complexities of insurance and provide new experiences to participants regarding techniques for evaluating and analyzing insurance problems. The final result of this FGD reconstructed a strategy to overcome the complexity and problems of the insurance industry, namely the need to create a Policy Guarantee Institution (LPP).